2015
DOI: 10.1517/14712598.2015.1052789
|View full text |Cite
|
Sign up to set email alerts
|

Metreleptin and generalized lipodystrophy and evolving therapeutic perspectives

Abstract: Metreleptin's approval for generalized lipodystrophy is the first step in defining and expanding its role to other metabolic diseases. Clinical trials are underway to delineate its efficacy in FPLD, human immunodeficiency virus/highly active anti-retroviral therapy-associated acquired lipodystrophy (HAL), and NAFLD. Additionally, there is growing data that support a therapeutic role in obesity. One of the barriers to development, however, is metreleptin's safety and immunogenicity. Further advances in biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 93 publications
(74 reference statements)
1
16
0
Order By: Relevance
“…The beneficial effects of leptin repletion on hepatic and peripheral insulin sensitivity, hepatic lipid content, and dyslipidemia in lipodystrophic and congenitally leptin-deficient states have been noted previously (22), though without the clear disassociation from changes in food intake that was achieved by Brown et al (6). The abrupt cessation of leptin in the subjects with generalized lipodystrophy may be viewed as physiologically similar to the disproportionate (to fat mass), sharp declines in circulating leptin concentrations that occur during fasting, which is a metabolic state that is largely nonresponsive to leptin (23).…”
Section: Leptin Physiology Is Metabolic Context Dependentsupporting
confidence: 58%
“…The beneficial effects of leptin repletion on hepatic and peripheral insulin sensitivity, hepatic lipid content, and dyslipidemia in lipodystrophic and congenitally leptin-deficient states have been noted previously (22), though without the clear disassociation from changes in food intake that was achieved by Brown et al (6). The abrupt cessation of leptin in the subjects with generalized lipodystrophy may be viewed as physiologically similar to the disproportionate (to fat mass), sharp declines in circulating leptin concentrations that occur during fasting, which is a metabolic state that is largely nonresponsive to leptin (23).…”
Section: Leptin Physiology Is Metabolic Context Dependentsupporting
confidence: 58%
“…The identification of these secondary phenotypes of PCOS is of importance also because these patients often benefit from tailored therapies, including specific dietary management as well as insulin sensitizers, particularly thiazolidinediones (pioglitazone) (69,72), which, however, requires the presence of residual adipose depots to achieve metabolic benefit. Finally, in patients with lipodystrophy and low levels of serum leptin, administration of recombinant human leptin may be dramatically beneficial in improving glycemic control, dyslipidemia and lipid accumulation in the liver (73). To conclude, the endocrinologists who deal with PCOS should be aware of the forms of PCOS secondary to SSIR as they are not so uncommon.…”
Section: Severe Insulin-resistant Syndrome and Pcosmentioning
confidence: 99%
“…Recombinant methionyl human leptin (r-met-HuLeptin) or simply metreleptin is a 146 amino acid (~16 kDa) protein that structurally is near-identical to the human leptin protein, except with the addition of a methionyl residue on the N-terminal domain of the tertiary protein structure ( Table 1 ). 11 , 12 , 27 Its action within the body mirrors that of the naturally occurring leptin hormone. However, the additional methionyl residue increases its half-life to approximately 3.8–4.7 hours, whereas previous studies have suggested that the half-life of a slower acting pool of leptin was 71 minutes.…”
Section: Metreleptinmentioning
confidence: 99%
“…Since leptin is a cytokine with the potential to alter CYP450 expression, 30 caution is warranted when prescribing metreleptin if the patient is simultaneously receiving drugs metabolized by CYP450, or if they are receiving metreleptin and are about to start a course of drugs metabolized by CYP450 with a narrow therapeutic index, such as oral contraceptives. 27 …”
Section: Metreleptinmentioning
confidence: 99%
See 1 more Smart Citation